Effects of student-owned and provided mobile devices on mathematical modeling competence: investigating interaction effects with problematic smartphone use and fear of missing out - Krause, Maurice; Greefrath, Gilbert; Forthmann, Boris; Kremer, Fabienne E.; Reer, Felix; Laumann, Daniel; Masemann, Dörthe; Denz, Cornelia; Heinicke, Susanne; Leibrock, Barbara; Marohn, Annette; Quandt, Thorsten; et al. (Frontiers in Education, 2024)
Nowadays, more and more digital resources are used in modern mathematical modeling classes. In order to access these resources, students need a suitable digital device—often mobile devices are used for this purpose. There are several concepts to enable students access to such devices. For example, students can be allowed to use their self-owned devices (Bring Your Own Device [BYOD] concept) or teachers can hand out school-owned devices to their students (device pool [pool] concept). Currently, little is known about possible effects of different mobile device access concepts on student learning. Hence, in this study, we investigated their effects on students’ mathematical modeling competence. In doing so, we also considered an interaction between the access concept and the effects of (a) students’ problematic smartphone use and (b) students’ fear of missing out on learning mathematical modeling. To this end, we conducted an experiment, measured students’ mathematical modeling competence as the outcome variable, and analyzed data of 263 German students in grades 8 and 9 using a multilevel model. In the experiment, students were randomly assigned to one of two study conditions and completed a mathematics modeling workshop. In the BYOD condition, students utilized their self-owned smartphones to work on the workshop tasks, whereas in the pool condition, students utilized institutionally provided smartphones. As a main finding, our results showed an interaction effect between the mobile device access concept and students’ problematic smartphone use on their competence (β=-0.24, 95% CI [-0.47,-0.01]). Students utilizing their self-owned smartphones were negatively affected by their problematic smartphone use (B=-1.45, 95% CI [-2.45,-0.46]), whereas students utilizing provided smartphones were not affected (B=0.04, 95% CI [-1.01,1.09]). Students with maximal problematic smartphone use achieved higher competences when utilizing provided devices (B_("BYOD" -"Pool" )=-1.20, 95% CI [-2.35, -0.05]). Our study demonstrates the importance of thinking about effects of student-owned and provided digital devices on mathematics learning. Finally, we discuss (a) that our results do not reveal a general preferability for one of the two access concepts, as well as (b) the relevance of student characteristics when choosing an access concept.